Treatment of invasive fungal diseases in cancer patients—Revised 2019 Recommendations of the Infectious Diseases Working Party (AGIHO) of the German Society of Hematology and Oncology (DGHO). Issue 7 (12th May 2020) - Ruhnke, Markus; Cornely, Oliver A.; Schmidt‐Hieber, Martin; Alakel, Nael; Boell, Boris; Buchheidt, Dieter; Christopeit, Maximilian; Hasenkamp, Justin; Heinz, Werner J.; Hentrich, Marcus; Karthaus, Meinolf; Koldehoff, Michael; et al.
Summary: Background: Invasive fungal diseases remain a major cause of morbidity and mortality in cancer patients undergoing intensive cytotoxic therapy. The choice of the most appropriate antifungal treatment (AFT) depends on the fungal species suspected or identified, the patient's risk factors (eg length and depth of granulocytopenia) and the expected side effects. Objectives: Since the last edition of recommendations for 'Treatment of invasive fungal infections in cancer patients' of the Infectious Diseases Working Party (AGIHO) of the German Society of Hematology and Medical Oncology (DGHO) in 2013, treatment strategies were gradually moving away from solely empirical therapy of presumed or possible invasive fungal diseases (IFDs) towards pre‐emptive therapy of probable IFD. Methods: The guideline was prepared by German clinical experts for infections in cancer patients in a stepwise consensus process. MEDLINE was systematically searched for English‐language publications from January 1975 up to September 2019 using the key terms such as 'invasive fungal infection' and/or 'invasive fungal disease' and at least one of the following: antifungal agents, cancer, haematological malignancy, antifungal therapy, neutropenia, granulocytopenia, mycoses, aspergillosis, candidosis and mucormycosis. Results: AFT of IFDs in cancer patients may include not only antifungal agents but also non‐pharmacologic treatment. In addition, the armamentarium of antifungals for treatment of IFDs has been broadened (eg licensing of isavuconazole). Additional antifungals are currently under investigation or in clinical trials. Conclusions: Here, updated recommendations for the treatment of proven or probable IFDs are given. All recommendations including the levels of evidence are summarised in tables to give the reader rapid access to key information.